Listening Awry: Lacan and the Electric Guitar at the Intersection of Music, Technology, and Identity - Jacob Morris (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
Contemporary positions on technology tend to emphasize that its import lies in its appropriation by a given social actor (group or individual), by how it is used. This paper does not categorically deny that such is often the case, but suggests that its inversion is widely overlooked. Overlooked, because much like the skull in Holbein’s The Ambassadors, evidence of technology’s active effect on the user is distorted until viewed from a particular vantage point. This paper takes Lacanian psychoanalysis as its vantage point and the musical technoculture of the electric guitarist as its object, revealing in the electric guitarist’s pursuit of identity through timbre that technology functions as the object-cause of desire, the objet petit a. Evidence of such an anamorphosis certainly supports the need for psychoanalysis in a critical musicology, but the larger implication is for thinkers of all disciplinary stripes to give technology a second look (or in this case a second listen) in order to move beyond the usual determinist, voluntarist, or even Luddite approaches.
Keywords: Lacan; Guitar; Music; Technology